Ultra-low field Magnetic Resonance Imaging of the human forearm in the Earths Magnetic Field of Dublin, Ireland. - Wetterling, Friedrich (My University, 2024)
The aim of this work was to explore the limits and opportunities for ultra-low field Magnetic Resonance Imaging in the earth’s magnetic field at 50T (EF-MRI) in Dublin, Ireland. MRI normally requires high static magnetic fields (>0.5T) to polarise the hydrogen-1 nuclei in tissue and to maximise the available signal. Callaghan et al. developed EF-MRI for use in antarctica [1] before advancing the technology to commercialisation as an educational systems globally [2]. Nowadays those systems can be developed at low material cost of less than 200EUR [3, 4]. However, their use has not evolved much beyond scientific and educational exploration. Some universities reported student laboratories for undergraduates using the system in physics [5] and in chemistry [6]. Yet, other examples demonstrated the remaining signal challenges to work with this approach in practice [
British and Irish Chapter of the International Society for Magnetic Resonance in Medicine
PUBLISHED
Nottingham, UK
Keywords: Smart & Sustainable Planet